Producent rolny wobec nieuczciwych praktyk handlowych – wybrane zagadnienia prawne - Lipińska, Izabela (Wydawnictwo Naukowe UAM, 2017)
The aim of this article is to define the legal scope of protection of the weakest players in the agri-food supply chain and to identify the role of the legislator in safeguarding their economic interests. The author notes that shortcomings in the functioning of the food supply chain are a global problem and there is no one effective instrument to strengthen the position of its weakest players. It is concluded that the voluntary and self-regulatory instruments proposed at European Union level partly contribute to ensuring fair market practices. It therefore appears necessary to introduce regulatory measures and public enforcement systems to combat unfair commercial practices. The law being currently implemented in Polish law largely satisfies this requirement.

L’articolo si propone di definire l’ambito di tutela giuridica nei confronti dei soggetti più deboli della filiera agroalimentare, nonché di specificare il ruolo del datore di lavoro nel garantire i loro interessi economici. L’autrice fa notare che i difetti presenti nel funzionamento della filiera agroalimentare costituiscono un problema globale e che uno strumento efficace per rafforzare la posizione dei soggetti più deboli non esiste. Concludendo, essa afferma che gli strumenti volontari e di autoregolazione proposti a livello UE contribuiscono in parte a garantire le pratiche di mercato oneste. Sembra pertanto necessario, al fine di prevenire le pratiche commerciali sleali, introdurre disposizioni regolamentari e sistemi pubblici di applicazione delle normative. La legge in corso di attuazione nel diritto polacco soddisfa ampiamente questo postulato.
Agricultural producer vis-à-vis unfair market practices – selected legal issues
Il produttore agricolo di fronte alle pratiche commerciali sleali – alcune questioni giuridiche scelte